Magic lantern empire : colonialism and society in Germany - Short, John Phillip, 1967- (Cornell University Press, 2012)
"Magic Lantern Empire examines German colonialism as a mass cultural and political phenomenon unfolding at the center of a nascent, conflicted German modernity. John Phillip Short draws together strands of propaganda and visual culture, science and fantasy to show how colonialism developed as a contested form of knowledge that both reproduced and blurred class difference in Germany, initiating the masses into a modern market worldview. A nuanced account of how ordinary Germans understood and articulated the idea of empire, this book draws on a diverse range of sources: police files, spy reports, pulp novels, popular science writing, daily newspapers, and both official and private archives.